Angular dependence of SiO2 etching in plasmas containing heptafluoropropyl methyl ether - Kim, Jun Hyun; Park, Jin Su; Kim, Chang Koo (Thin Solid Films, 2019)
SiO2 was etched in heptafluoropropyl methyl ether (HFE-347mcc3)/Ar and C4F8/Ar plasmas, separately, to evaluate the feasibility of the use of fluorinated ether plasmas as an alternative to perfluoro carbon plasmas. The etch rates of SiO2 in HFE-347mcc3/Ar plasma were higher than those in C4F8/Ar plasma because the O atoms in HFE-347mcc3 produced O radicals that reacted with fluorocarbons to produce volatile products, thus consuming more fluorocarbon films. In HFE-347mcc3/Ar plasmas, the changes in the normalized etch yield (NEY) with ion -incident angle followed nearly the same patterns at bias voltages higher than −600 V, while the NEY at −400 V was lower than those at other bias voltages. On the other hand, the NEYs of C4F8/Ar plasmas increased with bias voltage, indicating a strong dependence on the bias voltage. The characteristic changes in the NEY in HFE-347mcc3/Ar plasmas were correlated with the thickness and the fluorine-to‑carbon ratio of the steady-state film formed on the surface of the substrate.
Keywords: Angular dependence; Carbon plasmas; Etch rates; Fluorinated ethers; Fluorocarbon films; Angular dependence; Etch rate; Fluorinated ether plasma; Perfluoro carbon plasma; Steady-state fluorocarbon film